Implementation of Individualized distance learning programs for special needs childrens during the Covid-19 pandemic - Devia Sugmawati; Retno Winarni; Winarno Winarno (University of Muhammadiyah Malang, 2022)
Innovation of individual learning programs for children with special needs (ABK) in the middle of Emergency Remote Teaching (ERT) is necessary, especially for children with special needs. The purpose of this study was to describe the implementation of individual distance learning programs for children with special needs in inclusive schools during the pandemic. This is qualitative research with a phenomenological approach. Data collection techniques using observation sheets, interviews, and documentation. Data validation is done by source triangulation and technique triangulation. While the data analysis techniques use the theory of Miles and Huberman. The results of this study show the design of distance learning programs made by teachers to learn ABK in inclusive schools, namely with a collaborative model: (flexibility), (modification), (support), and with a 5M strategy. This collaboration Model and design help teachers and students in implementing the learning of children with special needs during the pandemic. In line with that, it is necessary to modify the individual learning program for children with special needs in inclusive schools the learning model that allows it to be used for learning for children with special needs during the pandemic is the 5M learning model.